Serangga Parasitoid pada Tanaman Kopi Varietas Tim-Tim (Coffea arabica x Coffea canephora) di Kabupaten Rusip Antara Aceh Tengah - Arini; Marlina; Aidil Amar (Pangale Journal of Forestry and Environment, 2026)
This study aimed to identify the composition, diversity, and evenness of parasitoid insects in the Tim-Tim coffee variety plantation ecosystem in Pilar Village, Rusip Antara District, Central Aceh Regency, as a basis for biological pest control. Data were collected using a purposive sampling survey method with three types of traps (light traps, yellow plate traps, and malaise traps), then analyzed using the Shannon-Wiener diversity index (H') and Pielou's evenness index (E). The results showed that 54 parasitoid individuals from 10 families were obtained, with Ichneumonidae as the dominant family. Light traps were the most effective in capturing parasitoids (25 individuals), followed by yellow plate traps (22 individuals) and malaise traps (7 individuals). The H' values ranged from 2.27–2.72 (moderate category), while the E values ranged from 0.96–1.00 (high category). It is concluded that the parasitoid community in the Tim-Tim coffee ecosystem has moderate diversity but high evenness, reflecting a stable community structure with potential to support sustainable biological control of coffee pests.